Impact of Second-Line Combination Treatment for Type 2 Diabetes Mellitus on Disease Control: A Population-Based Cohort Study - Dan Ouchi; Carles Vilaplana-Carnerero; Ramon Monfà; Maria Giner-Soriano; Ana Garcia-Sangenís; Ferran Torres; Rosa Morros (Adis, Springer Healthcare, 2023)
Abstract Background Type 2 diabetes mellitus is a chronic disease affecting millions of people worldwide. Achieving and maintaining glycemic control is essential to prevent or delay complications and different strategies are available as second-line treatment options for patients with type 2 diabetes who do not achieve glycemic control with metformin monotherapy. Objective The aim of this work is to describe the impact of initiating a combination treatment to reduce glycated hemoglobin in patients with type 2 diabetes with insufficient glycemic control. Methods We included patients with a type 2 diabetes diagnosis between 2015 and 2020 at the Information System for Research in Primary Care (SIDIAP) database in Catalonia, Spain. The primary outcome was the time to glycated hemoglobin control (≤ 7%) during the first 720 days, expressed as the restricted mean survival time. Adjusted differences of the restricted mean survival time were compared to analyze the performance of each treatment versus the combination with a sulfonylurea. Adherence was calculated as the medication possession ratio using an algorithm to model treatment exposure. Results A total of 28,425 patients were analyzed. The most frequent combinations were those with sulfonylureas and dipeptidyl peptidase-4 inhibitors. All treatments reduced glycated hemoglobin and the restricted mean survival time for the sulfonylurea treatment was 455 (451-459) days although combinations with glucagon-like peptide-1 and insulin reached glycemic control earlier, − 126 days (− 152 to − 100, p < 0.001) and − 69 days (− 88 to − 50, p < 0.001), respectively. Adherence was high in all groups apart from the insulin combination and had a significant effect in reducing glycated hemoglobin except in sodium-glucose cotransporter type 2 inhibitors and insulin. Glucagon-like peptide-1 and sodium-glucose cotransporter type 2 inhibitors showed significant reductions in weight. Conclusions Patients achieved the glycated hemoglobin goal with second-line treatments. Glucagon-like peptide-1 and insulin combinations achieved the goal earlier than sulfonylurea combinations. Adherence significantly reduced the time to glycated hemoglobin control except for the combination with sodium-glucose cotransporter type 2 inhibitors.